2018
DOI: 10.1051/e3sconf/20184500004
|View full text |Cite
|
Sign up to set email alerts
|

The anthropogenic pollutants in urban ponds based on the example of Słupsk

Abstract: Abstract. In areas of urban infrastructure, ponds play an important role. They are places of rest and recreation, and they facilitate contact between city dwellers and the aquatic environment. They are also a place for living waterflow and ichthyofauna. Urban ponds are susceptible to anthropogenic influences, and their self-cleaning capacity is limited due to their small size. The city of Słupsk is located in northern Poland. Coal combustion in domestic boilers and transport cause dust emissions to be released… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…It may be assumed in these cases that accumulation in the SML for V was determined by the load of atmospheric depositions, while for the other above-mentioned elements the share of the pollutants was more uniform between the sources from the hydrosphere and the atmosphere. The level of contaminants in urban water bodies such as ponds or lakes results from the sum of local factors as well as wet and dry deposition [17]. In this study, high accumulation of Ni and Cd was found in the SML layer in Człuchowskie Lake and Al in the ponds of the city of Słupsk.…”
Section: Discussionsupporting
confidence: 45%
See 4 more Smart Citations
“…It may be assumed in these cases that accumulation in the SML for V was determined by the load of atmospheric depositions, while for the other above-mentioned elements the share of the pollutants was more uniform between the sources from the hydrosphere and the atmosphere. The level of contaminants in urban water bodies such as ponds or lakes results from the sum of local factors as well as wet and dry deposition [17]. In this study, high accumulation of Ni and Cd was found in the SML layer in Człuchowskie Lake and Al in the ponds of the city of Słupsk.…”
Section: Discussionsupporting
confidence: 45%
“…Statistically significant correlations were also observed with elements found in trace concentrations. Al and F − are elements constituting urban pollutants, supplied via the atmosphere together with PM 10 and P 2.5 dusts [17]. This would explain the high content of Al and F − in the SML ponds of the city of Słupsk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations